Evaluation of usability problems of labor portal in Saudi Arabia - Alzuabi, Haifa Fahad; Alshaikhli, Imad Fakhri Taha (Helvetic Editions LTD, Switzerland, 2013)
The purpose of this research was to evaluate the quality of Labor portal. Ministry of Labor focused on over the past years to establish a database of the labor market in the Kingdom of Saudi Arabia. The data includes workers in Saudi private sector, whether Saudis or expatriates where mechanization included all labor of 39-office work in various regions. The governorates of the Kingdom operates IT management to develop this rule to get the information and data related to the labor market quickly and accurately. 7 experts evaluated the quality portal of Saudi Arabia Ministry of Labor using self-developed instrument containing eight factors from the literature review on 5-likert scale. The result of the study shows that, the Labor portal quality is fairly good by 78.2% and it needs further improvement and development by 21.8%. Suggestions were made to the Saudi government, particularly, the Saudi Ministry of labor that, there is a need to further test the portal empirically based on the experts’ evaluation.